FROM INFLUENCE TO EXPLOITATION: UNVEILING CORRUPTION DYNAMICS IN THE PALM OIL INDUSTRY - Wardhani, Sari; Putri, Ni Made Martini (International Journal of Social Service and Research, 2024)
This study examines the complexity of corruption networks in the palm oil industry, focusing on the roles of state and corporate actors upstream and downstream. Using Social Network Analysis (SNA) of two corruption cases with data from investigation reports and court decisions, key actors and their relationships are analysed through degree centrality, eigenvector and modularity metrics. The results identified that actors have various roles, such as organisers, influencers, intermediaries, or simply communicators. Corporate actors dominate in upstream corruption involving illegal palm oil licences. Corporate actors dominate as initiators, exploiting regulatory weaknesses with state facilitation. In contrast, corruption in downstream palm oil revolves around crude palm oil (CPO) export fraud, with state actors as initiators organising systemic collusion so that corporate actors benefit from the manipulated system. The findings reveal adaptive corruption networks characterised by hierarchical structures and reciprocal solid relationships between actors. The study highlights the systemic nature of corporate-state crime in the palm oil industry by emphasising the dynamic role of influence and exploitation. Interventions against corruption cannot take a dyadic approach but must be comprehensive by disrupting corruption networks in weak governance.